If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 11 = 2x + 5 Reorder the terms: 11 + x = 2x + 5 Reorder the terms: 11 + x = 5 + 2x Solving 11 + x = 5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 11 + x + -2x = 5 + 2x + -2x Combine like terms: x + -2x = -1x 11 + -1x = 5 + 2x + -2x Combine like terms: 2x + -2x = 0 11 + -1x = 5 + 0 11 + -1x = 5 Add '-11' to each side of the equation. 11 + -11 + -1x = 5 + -11 Combine like terms: 11 + -11 = 0 0 + -1x = 5 + -11 -1x = 5 + -11 Combine like terms: 5 + -11 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| (5x+4)-(2x-4)= | | x+13=3x+3 | | x-1=3x+5 | | 120-5x=13x+16 | | 132-5x=22x+15 | | 5a=45+2q | | 12-8x=48-22x | | y=x^2+3x+1 | | 10+4x=22 | | 6x^2=39x-45 | | 0=x^2(x^4+6x^2-16) | | 12x+24=8x+4 | | -2x-13=x+2 | | -2-13=x+2 | | 6-10x=66-45x | | -x^2+18x+19=0 | | 2x+6=x+1 | | 5x+10y= | | ln(3x)+ln(5)=2 | | 2x-2=x+6 | | 7x+22=5x+50 | | 6-10x=46-24X | | 5x^2+26x+24= | | 4n-5=27 | | -3x-4=x+24 | | 5a-40=a | | 10x-118=4x-10 | | -2(3x)= | | 3x+19=2x | | x-9=4x+3 | | x-9=-6 | | 4y=9y-20 |